Vulvodynia – a multidisciplinary problem - K. R. Bakhtiyarov; P. V. Budanov; V. A. Pronina; E. V. Virivskaia (Бюллетень сибирской медицины)
This literature review is devoted to the problem of vulvodynia. The article summarizes information about the etiology and pathogenetic factors of this syndrome, touches the aspects of diagnosis and treatment of this form of chronic genital pain. Despite the prevalence of this pathology, women with pain in the vulva often remain undiagnosed and do not receive adequate therapeutic and psycho-emotional support. Currently, the focus is in searching of the definition, classification, prevalence, pathophysiological factors of occurrence and adequate personalized therapy of this nosology.